Analisis Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Ukuran Dewan Direksi, Dan Ukuran Dewan Komisaris Terhadap Biaya Keagenan - Fitri Laela Wijayati (EBBANK, 2015)
Agency problem appears because of conflict interest between managers as a agen and firm’s owner as a principal. Conflict of interests between the firm’s managers and the firm’s owners causes agency cost. Prior study demostrated that ownership structure and board structure can reduce agency cost. This study aims to analyze the effects of managerial ownership, institutional ownership, board of director size, and board of commissioner size on agency cost. Agency cost as a dependent variable in this study measured by total asset turnover and operating expense ratio. This paper based on the previous research by Ang et al. (1999), Singh et al. (2003) and Faisal (2004). Sample of this study consist of firms listed in Indonesian Stock Exchange in 2009-2013. The sampling method that used in this study is purposive sampling method consist of 195 observation. Hypothesis testing using multiple regression analysis. This study found that managerial ownership and board of commissioner size do not have significant effects on reduce agency cost. Institutional ownership and board of director size have significant effects on reduce agency cost.